Well-Posedness and Analyticity of Solutions to the Parabolic-Elliptic System of Drift-Diffusion Type in Fourier-Besov Spaces with Variable Exponents - Azanzal, Achraf; Allalou, Chakir; Melliani, Said (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we study the Cauchy problem of the Debye-Hückel system with initial data in variable Fourier-Besov spaces. By using littlewood-Paley decomposition, we obtain the global well-posedness result for small initial data belong to critical variable exponent Fourier-Besov spaces. Moreover, we get the analyticity of global solutions.